Microscopia confocal reflectante a laser na avaliação da resposta terapêutica da ceratose actínica com 5-fluorouracila tópica a 5%: estudo comparativo com o exame anatomopatológico - Ishioka, Priscila [UNIFESP] (2018)
Background: Histological examination is the gold standard for actinic keratosis diagnosis; however, it is not always a feasible approach. Reflectance confocal microscopy (RCM) is a noninvasive technique that may be an alternative for monitoring actinic keratoses treatment response. Topical 5fluorouracil is indicated for actinic keratosis multiple lesions and for field cancerization treatment. Objectives: To assess the RCM accuracy, sensibility and specificity for actinic keratosis, considering as a goldstandard the histopathological examination; as well as to evaluate the efficacy of 5% 5fluorouracil treatment. Methods: This is a prospective study in actinic keratosis patients between August, 2014 and November, 2015. RCM analyses were performed in one randomly selected actinic keratosis lesion of the upper limbs by two independent observers before and after 5% 5fluorouracil treatment. At the end of treatment and with clinical bleaching of treated lesions, histological examination was performed by two pathologists. Results: A total of 50 lesions were enrolled, and 40 lesions presented complete clinical bleaching after treatment and were included in the final analysis. Accuracy, sensibility and specificity means among observers were 83.8%, 84.6% and 83.3%, respectively. After 5fluorouracil treatment, actinic keratosis was diagnosed in 45.0% (observer 1) and 32.5% (observer 2) of subjects according to RCM and in 32.5% of subjects according to histological examination. Considering RCM observers diagnosis, the concordance was substantial (k 0,637, p<0,001). 5fluorouracil led to a reduction in 55.0%67.5% of actinic keratoses according to RCM analysis. Conclusion: This study allows to validate of RCM as a noninvasive method capable of monitoring actinic keratosis therapeutic response to 5fluorouracil, presenting efficacy comparable to histological examination. Additionally, the results suggest that 5fluorouracil may be a satisfactory option for therapeutic control of this condition.